Kartu identifikasi gigi, cara sederhanamenggabungkanepidemiologi, kedokteran gigi pencegahandankedokterangigi forensikpadaanak (Dental identificationcard, a simple method to unify epidemiology, preventive dentistry, and forensic dentistry in children ) - Ignatius Setiawan; Grace Monica; Winny Suwindere (DiscoverSys Inc., 2014)
Natural disasters, crime, and accidents can happen anytime. The hardest part after the tragedy is to identify the victim,especially if their bodies are no longer intact. Tooth is one of the most important parts of the body that can beidentified even if the body is already destroyed. One of the difficulties in the identification process is the inadequacy ofante mortem data of the victims, especially the children. In this paper, it discussed about dental ID card that can beuseful as summary information on cases of abduction or in the process of identifying the bodies in the event of adisaster. Odontogram in the dental identification card can help the dentist to create a plan of care for children and canalso assist in the gathering of data for epidemiological purposes that give data about the health condition of the child'smouth. Such data can be used as a basis for policy-making is a step to prevention, which is expected to improve theoral health of children in Indonesia. This card must be given to the patient and always taken when they go to thedentist. All providers of oral health services, including UKGS role in updating the data on a regular basis. It was concluded that the oral health information is very helpful in making the right decisions that improve oral health.Dental identification card is a real little effort in realizing it, have a major impact, simple but useful.